(untitled) (World Bulletin of Social Sciences, 2023)
This article reflects archaeological materials and literature on the problems of developing cultural and economic ties between the tribes of Central Asia and the steppes of Eurasia, which most clearly occurred in the Bronze Age after the migration of the steppe tribes from north to south. In addition, the article reveals the socio-economic and cultural life of the resettled population, as well as the problems of the migration movement of the Bronze Age tribes